Scope of Laparoscopic Cholecystectomy in Patient with History of Previous Upper Abdominal Surgery - Muhammad Zeb, Muhammad Zarin, Ijaz Ahmad Khan, Samiullah, Muhammad Younas Khan, Kaleemullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: In recent years, laparoscopy’s role in treating benign gallbladder and biliary tract diseases has been well confirmed. Objective: The main objective of the study is to find the scope of laparoscopic cholecystectomy in patient with history of previous upper abdominal surgery. Material and methods: This retrospective study was conducted in khyber medical center Peshawar during June 2022 to December 2022. An informed consent was obtained from each patient included in the study. The primary outcomes of the current study involves incidence rate of intraoperative biliary injury and the secondary outcome of the study includes postoperative strictures, bile leaks, hernia, infections, postoperative need for reoperation or drainage. Results: A total of 316 cholecystectomies were performed. Out of these 28 were performed with other hepatobiliary or bariatric operations. The remaining subjects 288, out of which 212 did not show severe cholecystitis and the remaining 76 had severe cholecystitis. 51 patients with severe cholecystitis had LC and 22 were treated with LSC out of those 3 went through open cholecystectomy and were excluded from the study. Practical Implication: This study will helps us in hospitals in Laparoscopic cholecystectomy because it’s a safe method and procedure. Conclusion: It is concluded that Laparoscopic cholecystectomy is a feasible and safe treatment for symptomatic gallstone disease in selected patients with previous upper abdominal surgery history. Keywords: Laparoscopic cholecystectomy, Procedure, Patients, Abdominal